Home range size decreases with increasing site fidelity in high-density subpopulations of brown trout. Issue 5 (3rd September 2019) - Slavík, Ondřej; Horký, Pavel
Abstract : The home range (HR) of wild animals increases with individual body size and is smaller in high density populations in productive areas. If sufficient resources are available, animals often display sedentary behavior. The return and reuse of an environment by individuals is frequently termed "site fidelity". Smaller HR size and high site fidelity have been reported especially in mammals. In the present study, we explored this relationship in adults of subpopulations of the brown trout Salmo trutta, which typically exhibits HRs. The HR size of conspecifics from subpopulations characterized by density and subpopulation site fidelity was determined by radio-telemetry during a 7-year study. We found smaller HR sizes in subpopulations with higher site fidelity. Moreover, HR size was found to increase with body mass and decrease with subpopulation density across seasons. The results showed that the HR size of wild brown trout varies with subpopulation density and site fidelity.